Protective Effects of Human Nonrenal and Renal Stromal Cells and Their Conditioned Media in a Rat Model of Chronic Kidney Disease. (27th November 2020) - Imberti, Barbara; Cerullo, Domenico; Corna, Daniela; Rota, Cinzia; Locatelli, Monica; Pezzotta, Anna; Introna, Martino; Capelli, Chiara; Carminati, Claudia Elisa; Rabelink, Ton J.; Leuning, Danielle G.; Zoja, Carlamaria; et al.
Mesenchymal stromal cells (MSCs) are emerging as a novel therapeutic option for limiting chronic kidney disease progression. Conditioned medium (CM) containing bioactive compounds could convey similar benefits, avoiding the potential risks of cell therapy. This study compared the efficacy of nonrenal and renal cell-based therapy with the corresponding CM in rats with renal mass reduction (RMR). Infusions of human kidney stromal cells (kPSCs) and CM-kPSCs, but not umbilical cord (uc) MSCs or CM-ucMSCs, reduced proteinuria and preserved podocyte number and nephrin expression in RMR rats. Glomerular fibrosis, microvascular rarefaction, and apoptosis were reduced by all treatments, while the peritubular microvascular loss was reduced by kPSCs and CM-kPSCs treatment only. Importantly, kPSCs and CM-kPSCs reduced NG2-positive pericytes, and all therapies reduced α-smooth muscle actin expression, indicating reduced myofibroblast expansion. Treatment with kPSCs also significantly inhibited the accumulation of ED1-positive macrophages in the renal interstitium of RMR rats. These findings demonstrate that the CM of ucMSCs and kPSCs confers similar renoprotection as the cells. kPSCs and CM-kPSCs may be superior in attenuating chronic renal injury as a cell source.